Frontispiece: Trends and Prospects of Bimetallic Exsolution. Issue 22 (17th April 2021) - Tang, Chenyang; Kousi, Kalliopi; Neagu, Dragos; Metcalfe, Ian S.
Abstract : Exsolution is a relatively new research hotspot which can be traced back to 2002. In the Minireview on page 6666, C. Tang, K. Kousi, D. Neagu, and I. S. Metcalfe review the, approximately, 70 studies published so far, on bimetallic exsolution and identified research trends in this area. It has been demonstrated that exsolution can endow bimetallic particles with advantages in the terms of high catalytic activity, improved electrochemical properties, prolonged durability and strong resistance to deactivation in a wide range of applications mainly including electrochemistry and catalysis.